2021
DOI: 10.3390/cells10092442
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Characterization of a Novel Gill Cell Line, LG-1, from Atlantic Lumpfish (Cyclopterus lumpus L.)

Abstract: The use of lumpfish (Cyclopterus lumpus) as a cleaner fish to fight sea lice infestation in farmed Atlantic salmon has become increasingly common. Still, tools to increase our knowledge about lumpfish biology are lacking. Here, we successfully established and characterized the first Lumpfish Gill cell line (LG-1). LG-1 are adherent, homogenous and have a flat, stretched-out and almost transparent appearance. Transmission electron microscopy revealed cellular protrusions and desmosome-like structures that, toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In cultured primary hepatocytes of carp (Cyprinus carpio), exposure to 20 nM for 18 h led to a 30-fold increase in the EROD rate [36]. A primary cell culture from rainbow trout (Oncorhynchus mykiss) liver showed a dose-dependent EROD rate increase (maximum nine-fold) after exposure to 3.6 to 360 nM BNF for 48 h [37], which is comparable to the results observed for ASG-10 in the present study and the gill cell line (LG-1) of Atlantic lumpfish (Cyclopterus lumpus) [17]. In contrast, CYP1A activity was not detectable in the gill cell lines RTgill-W1 of rainbow trout and G1B of walking catfish [15].…”
Section: Cyp Activities In Asg-10supporting
confidence: 87%
See 1 more Smart Citation
“…In cultured primary hepatocytes of carp (Cyprinus carpio), exposure to 20 nM for 18 h led to a 30-fold increase in the EROD rate [36]. A primary cell culture from rainbow trout (Oncorhynchus mykiss) liver showed a dose-dependent EROD rate increase (maximum nine-fold) after exposure to 3.6 to 360 nM BNF for 48 h [37], which is comparable to the results observed for ASG-10 in the present study and the gill cell line (LG-1) of Atlantic lumpfish (Cyclopterus lumpus) [17]. In contrast, CYP1A activity was not detectable in the gill cell lines RTgill-W1 of rainbow trout and G1B of walking catfish [15].…”
Section: Cyp Activities In Asg-10supporting
confidence: 87%
“…CYP1A converts 7-ethoxyresorufin to resorufin, which can be measured by fluorescence spectroscopy [ 16 ]. The assay was performed as described in [ 17 ], with minor modifications. Briefly, the cells were seeded in a black 96-well plate as described in Section 2.2 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, while the cyp1A1 gene was expressed at a considerably lower level in the cell line (Log2fc −4.4), exposure of the ASG-10 cells to β-naphthoflavone, a known inducer of CYP1A ( Heinrich et al, 2014 ), induced both CYP1A protein expression and activity ( Ivanova et al, 2023 ). Also, the gill cell line LG-1 from Atlantic Lumpfish ( Cycloperus lumpus L) was found to have inducible CYP1A activity ( Sindre et al, 2021 ), while the gill cell line from rainbow trout (RTgill-W1) and Waking catfish ( Clarias batrachus ), GB1, had no detectable CYP1A activity after β-naphthoflavone treatment ( Franco et al, 2018 ). Interestingly, while expression of several of the cyp genes such as cyp1A1 is well characterized in Atlantic salmon gill ( Olsvik et al, 2015 ; Alderman et al, 2020 ), many of the cyp genes emerging from the transcriptomics data are reported here in Atlantic salmon gill for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while the cyp1A1 gene was expressed at a considerably lower level in the cell line (Log2fc −4.4), exposure of the ASG-10 cells to β-naphthoflavone, a known inducer of CYP1A (Heinrich et al, 2014), induced both CYP1A protein expression and activity (Ivanova et al, 2023). Also, the gill cell line LG-1 from Atlantic Lumpfish (Cycloperus lumpus L) was found to have inducible CYP1A activity (Sindre et al, 2021), while the gill cell line from rainbow trout (RTgill-W1) and Waking catfish (Clarias batrachus), GB1, had no detectable CYP1A activity after TABLE 6 (Continued) Profile of biotransformation gene expression and proteins detected in ASG-10 relative to gill: Log2fc for genes expressed with significant differences: −0.3 to −12.7 (lower); 0.2 to 9.0 (higher).…”
Section: Biotransformationmentioning
confidence: 99%